OIL AND GAS BEARING COMPLEXES AND LITHO-STRATIGRAPHIC CHARACTERISTICS OF PLIOCENE DEPOSITS OF THE BULLA-DENIZ FIELD - POGORELOVA, Elena; ABDULLA-ZADA, Murad (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. In the current and long-term plans for the development of the country's fuel and energy balance, there is a significant emphasis on increasing and objectively assessing hydrocarbon resources to ensure a steady rise in oil and gas production. A decrease in geological exploration in the South Caspian basin has been observed, partly due to overestimates of predicted resources made before the twentieth century, which may have overly optimistic characterizations of the oil and gas potential of various regions and areas. In the Baku Archipelago, industrial deposits have been discovered in several geological horizons, with stratal deposits mainly associated with crestal tectonically shielded areas. A characteristic feature of the Productive Series (PS) section is the regular replacement of oil accumulations with gas and gas condensate in the direction of regional layer immersion.Methods. The purpose of the study is to clarify and evaluate the prospects of oil and gas-bearing deposits within PS sediments. This involved analyzing a complex of geological and geophysical materials to determine the reservoir properties of these sediments. The study incorporated stock materials, published articles, and factual data. An inter-well correlation was performed based on well data to assess the reservoir properties of PS sediments. The geological structure, lithological confinement, and petrophysical features of the deposits were also examined.Results. The analysis of the V horizon of the Bulla-Deniz field revealed that the section is predominantly clay (91 %) rather than sandy (9 %). The porosity of the section varies from 2 to 16 %, while the gas saturation parameter ranges between 0.47 and 0.61. The VII horizon, in contrast, has a relatively less clayey composition, which positively influences the reservoir parameters.Conclusions. The study highlights the need for a more nuanced evaluation of hydrocarbon resources in the South Caspian basin, specifically within the Baku Archipelago. The results indicate that the Productive Series (PS) sediments, particularly in the V horizon of the Bulla-Deniz field, present significant challenges due to their high clay content and variable porosity and gas saturation. However, the VII horizon's relatively better reservoir properties suggest that targeted exploration and development efforts could yield promising results. To optimize future resource assessment and exploitation, it is essential to integrate updated geological and geophysical data with modern exploration techniques. This approach will ensure a more accurate understanding of the region's hydrocarbon potential and contribute to the sustainable management of its oil and gas resources.
Keywords: South Caspian basin; Baku archipelago; Bulla deniz; field; pliocene; Productive Serie; sediment